UJI EFEKTIVITAS ANTIBAKTERI DENGAN KULIT BUAH ALPUKAT(Persea americana Mill) SEBAGAI OBJEK UNTUK DIAMBIL EKSTRAKNYA DENGAN BIOINDIKATOR BAKTERI Staphylococcus aureus - Mirna Jayustin; Ade Putra Fratama (Universitas Negeri Medan, 2019)
Avocados are known as antibacterial because of the content of antibacterial compounds such as saponins, alkaloids, and flavonoids in the fruit and leaves. Avocado extract skin has a higher content of carotene, total phenolic and flavonoids than the fruit meat. Total phenolic content and antioxidant potential of avocado phenol are influenced by solvent extract and avocado type. The skin and seeds have a higher phenolic content than the fruit flesh. Avocado skin and seeds also have greater antioxidant ability in test tubes. Phenolic compounds found showed antioxidant activity in vitro. This study aims to determine whether avocado bark extract has antimicrobial activity against Staphylococcus aureus bacteria. This research is an experimental study using disc diffusion. The results of this study found testing of lemongrass leaf extract (Cymbopogonnardus) with a concentration of 25%, 50%, 75%, 100%, influencing the growth of Staphylococcus aureus bacteria. This study shows that avocado peels affect the growth of Staphylococcus aureus bacteria.